Analysis Of Tourism Development In Improving Community Welfare In Nias Selatan District, North Sumatera Province - Zalukhu, Berkat Dedikasi; Sirojuzilam, Sirojuzilam; Revida, Erika; Purwoko, Agus (International Conference on Sciences Development and Technology, 2023)
This Article focuses on the analysis influence development tourist to a well-being community in the Regency South Nias, North Sumatra Province. Study This aims To know the extent of development tourists can contribute to the enhancement well-being public local. Development tourism in the Regency South Nias has become a priority in the effort to increase the income original region and the welfare public. Object tourism in South Nias has interesting Lots of tourists, potentially increasing income and welfare, public local. Study This uses method descriptive quantitative For collect and analyze data. Data is collected through surveys, and interviews. Research results show that the development of tourist influence is positive for the well-being public. This matter is seen from the enhanced income original area and the absorption of power work in the sector tourist. Study this is also found that development tourists must consider the impact on the ecosystem coast and sources of Power natural. Therefore, appropriate strategies and policies are needed To ensure that the development of tourist sustainability can be done without damaging the environment and sources of Power nature. Overall, research gives proof that the development of tourism can contribute to the enhancement of the well-being community in the Regency South Nias, North Sumatra Province. Required more Lots study For understand more carry on about How development tourist can be done with a sustainable and profitable way for all parties involved.